An investigation on the population parameters of freshwater crayfish (Astacus leptodactylus Esch., 1823) in Lake İznik (Bursa) - Aydın, Hamdi; Harlıoğlu, Muzaffer Mustafa; Deniz, Tomris (My University, 2015)
Length weight relationships, distribution of length and weight groups, sex ratio, and length compositions of the crayfishAstacus leptodactylus (Esch., 1823) population in Lake İznik (Bursa), along with some reproductive-period characteristics (spawningperiods, pleopod egg numbers, and egg incubation periods), were investigated between February 2010 and May 2011. For this purpose,1897 freshwater crayfish samples (896 female, 1001 male) were collected, using fyke nets of 34-mm nominal bar length. It was observedthat females carried pleopodal eggs during the second week of January, and they carried first-stage juveniles during the second week ofJune. Individuals within the 76 149 mm total length group had approximately 239.95 ± 109.36 pleopod eggs; egg diameter was 2.763± 0.150 mm. The mean total length of the individuals was 104.17 ± 14.89 mm for females and 95.71 ± 13.11 mm for males. The meanweight was 32.50 ± 21.83 g for females and 28.82 ± 14.12 g for males. As a result of regression analyses, the length weight relationshipwas calculated as W = 3.10 5 TL3.011 for females and W = 8.10 6 TL3.3016 for males. These findings show that females of A. leptodactylushave isometric growth, but males of this species have positive allometric growth. This study reveals that the A. leptodactylus populationof Lake İznik demonstrates recovery in its situation.
Keywords: Biyoloji; Deniz ve Tatlı Su Biyolojisi; Zooloji